"Factores biosocioculturales maternos y nivel de conocimiento sobre lactancia materna. Servicio de maternidad del Hospital Belén de Trujillo, 2008" - Bernales Espinoza, Cynthia Marianella (2009)
This research study of descriptive correlational cross was met with mothers in the maternity service for Trujillo's Hospital Bethlehem, during the months of September to November of 2008, with the purpose of determining the influence of factors biosocioculturales: Age, parity, educational level, origin, occupation, marital status at the level of knowledge of mothers in the maternity service for Trujillo's Hospital Bethlehem. The sample consisted of 208 mothers, who were selected according to criteria of inclusion. Data collection was obtained by the instrument known as: Scale for measuring the level of knowledge about breastfeeding (EMNCSLM), applied through personal interviews, taking into account the principles of anonymity and reliability. The data obtained were tabulated, processed in SPSS version presented in tables 15 and single and double entry, with digital frequencies and percentages, as well as graphics. The analysis of the influence of factors, was conducted through the test of independence criteria Chi-square (X2). Found the following conclusions: Of the total mothers in the survey, 48.1 percent are between the ages of 26 to 30 years, 52.4 percent have more than one child, 44.7 percent have a secondary level of education, 65.4 percent of the mothers come from the coast, 79.8 percent of mothers do not work, and 72.1 percent of mothers are cohabiting. The 86.5 percent of mothers have regular level of awareness about breastfeeding. The age and parity are the factors biosocioculturales presenting statistical significant at the level of awareness about breastfeeding.